Coccinellid Predators of Aphid and Their Phylogenetic Analysis Using COI Gene Sequences - Rain, Faria Farhana; Aslam, Abu Faiz Md.; Ringki, Habiba Sultana; Sultana, Nahida; Akter, Nayma; Howlader, Abdul Jabber (International Journal of Applied Sciences and Biotechnology, 2016)
An extensive survey of aphid predatory Coccinellid beetles (Coleoptera: Coccinellidae) was conducted in Jahangirnagar University campus, Savar during October 2014 to March 2016. Total nine ladybird beetles viz, Adalia bipunctata, Coccinella septempunctata, Coccinella transversalis, Cycloneda munda, Harmonia axyridis, Hippodamia convergens, Micraspis discolor, Scymnus nebulosus, Sticholotis sp. were identified as predators of aphid. Among them, Micraspis discolor was most abundant predator. Biology and bio-control potential of M. discolor was studied in laboratory condition on bean infesting aphid (Aphis fabae). The maximum predation was 102±1.83 observed in 4th instar larvae of M. discolor. Along with biological study, phylogenetic relationship of ladybird beetles was constructed based on mitochondrial COI gene. Out of nine identified coccinellids, five species showed more conserve region than the rest in alignment. The interspecific genetic distance ranges for nine beetles were very low (0.15-0.24). Higher interspecific genetic diversity recorded for H. axyridis. The phylogenetic tree was created and analyzed using both Neighbour Joining and Maximum likelihood methods to define the origin and evolutionary relationships of the species. Molecular analysis demonstrated that evolution of these species has been occurred from a common ancestor. Such study of ladybird beetles would be helpful in biological control program of aphid pest. Int J Appl Sci Biotechnol, Vol 4(3): 408-416